Bone morphogenetic protein signaling in distal patterning and intercalation during leg regeneration of the cricket, Gryllus bimaculatus. (24th July 2018) - Ishimaru, Yoshiyasu; Bando, Tetsuya; Ohuchi, Hideyo; Noji, Sumihare; Mito, Taro
Abstract : The cricket, Gryllus bimaculatus, is a classic model of leg regeneration following amputation. We previously demonstrated that Gryllus decapentaplegic ( Gb ' dpp ) is expressed during leg regeneration, although it remains unclear whether it is essential for this process. In this study, double‐stranded RNA targeting the Smad mathers‐against‐dpp homolog, Gb ' mad, was used to examine the role of bone morphogenetic protein (BMP) signaling in the leg regeneration process of Gryllus bimaculatus . RNA interference (RNAi)‐mediated knockdown of Gb ' mad led to a loss of tarsus regeneration at the most distal region of regenerating leg segments. Moreover, we confirmed that the phenotype obtained by knockdown of Dpp type I receptor,   Thick veins ( Gb ' tkv ), closely resembled that observed for Gb ' mad RNAi crickets, thereby suggesting that the BMP signaling pathway is indispensable for the initial stages of tarsus formation. Interestingly, knockdown of Gb ' mad and Gb ' tkv resulted in significant elongation of regenerating tibia along the proximodistal axis compared with normal legs. Moreover, our findings indicate that during the regeneration of tibia, the BMP signaling pathway interacts with Dachsous/Fat ( Gb 'Ds/ Gb 'Ft) signaling and dachshund ( Gb ' dac ) to re‐establish positional information and regulate determination of leg size. Based on these observations, we discuss possible roles for Gb ' mad in the distal patterning and intercalation processes during leg regeneration in Gryllus bimaculatus . Abstract : The cricket, Gryllus bimaculatus, is a classic model of leg regeneration following amputation. In this study, we showed that RNA interference (RNAi)‐mediated knockdown of BMP signaling components led to a loss of tarsus regeneration and the elongation form of regenerating tibia. We conclude that the BMP signaling pathway regulates the distal patterning and intercalation processes of leg regeneration in Gryllus bimaculatus .